Treaty, law and covenant in the Ancient Near East - Kitchen, Kenneth Anderson, 1932- (Wiesbaden)
3 c. (xxvi, 1086 s. ; xix, 268 s. ; xiv, 288 s.)
Keywords: "This work presents a far-reaching social profile of life in the Ancient Near East, based on its wealth of law-collections, treaties and covenants through three millennia. Volume 1 (The Texts) sets out a uniquely comprehensive corpus of over 100 such documents in 10 languages, mostly displayed in facing-page transliterations and English translations with individual bibliographies. Volume 2 (Text, Notes, and Chromograms) provides essential philological and background commentary to the texts, fully indexes their subject-matter, and concludes with a revolutionary and innovative series of full-colour diagrams of every text, vividly highlighting variations through the centuries. Finally, Volume 3 (Overall Historical Survey) outlines the flowing interplay of political history, changing social norms and varying documentary formats throughout the whole period. Taken together, this tryptich offers a striking and indispensable new overview of its multifaceted world for Ancient Near-Eastern and biblical studies." --